The Role of Public Relations in the Television Series "The Boys" - Rudi Alfianto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The television series "The Boys" is a series that tells the story of improving the image of a hero by a public relations practitioner. This television series also raises the issue of the life of a hero in the eyes of the public and the media who have a bad image. The purpose of this research is to find out the role of public relations in the character Ashley J. Barrett, played by Colby Minifie in the television series "The Boys". The research method used by researchers is a qualitative method, with a semiotic approach, namely a science that studies signs. The theory used focuses on the level of reality, the level of representation, and the level of ideology of John Fiske's television codes. In this research, the data collection techniques used were literature study, observation and documentation. The results of this research conclude that at the reality level it can be seen in the form of the behavior and appearance of Ashley J. Barrett's character, who is an expert communicator and expert advisor who carries out persuasive communication, showing the role of public relations, and Ashley J. Barrett's appearance tends to be stable when meeting with the public , namely by wearing a formal suit. The level of representation in the form of camera code and dialogue code, and the level of ideology can be seen from the ideology that appears in the television series "The Boys", there is discrimination between the black race and the white race and based on point eight of the international public relations code of ethics.